PURWARUPA ROBOT LENGAN PEMILIH BARANG BERDASARKAN WARNA - , HABIB NOOR IRFANI, Isnan Nur Rifai, S.Si., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Designed a robot with five degeree of freedom with gripper as effector. The robot arm used for sorting items by colour of items. The system consists of a colour sensor, Arduino UNO, and five servo motors as actuators robotic. The sensor consists of a colour receiver LDR as a reflection of the emitted light intensity LED super bright to a colour object. These sensors detect the object that result a colour sensor readings will be processed through the Arduino UNO.Determination position of the object put into place by the colour of the object using the mapping area metod. The position is set manually and then saved to the Arduino UNO as a reference for the robot arm motions. From the results, the robot arm can pick up and put things exactly and the response time of robot arm to the red object for 9,5 sec, green object for 14,25 sec, blue object for 14,20, and yellow object for 14,58 sec.